The effectiveness of salesmanship in influencing customer buying decision at Sime UEP Properties Sdn Bhd / Noor Suhana Baharum - Baharum, Noor Suhana (2007)
The objective and scope of the study is to identify the factors that contribute to the effectiveness of salesmanship in influencing customer buying decision at Sime UEP Properties Sdn. Bhd. There are four factors that contribute to this problem which is personal selling, relationship strategy, product strategy and customer strategy. So from the study the researcher wants to know whether the factors have relationship or not in customer buying decisions.